2006
DOI: 10.1021/ac060250j
|View full text |Cite
|
Sign up to set email alerts
|

The Genoa 2005 Outbreak. Determination of Putative Palytoxin in MediterraneanOstreopsisovataby a New Liquid Chromatography Tandem Mass Spectrometry Method

Abstract: A new method for sensitive, specific, and direct determination of palytoxin is proposed herein. It is based on combination of reversed-phase liquid chromatography with mass spectrometry (LC-MS). The new method was set up on a turbo ion spray-triple quadrupole MS instrument operating in selected ion monitoring (SIM) and multiple reaction monitoring (MRM) acquisition modes (positive ions). The minimum detection levels for matrix-free toxin on column were thus estimated from the data to be 200 and 125 pg in SIM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
198
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(214 citation statements)
references
References 15 publications
6
198
1
4
Order By: Relevance
“…The most informative results were obtained by interpretation of MS n spectra of the triply-charged ion of m/z 906.8; this ion, previously assigned to [M + 2H + K] 3+ [18], had to be reassigned since most of the fragments contained in its MS n spectra were not consistent with any reasonable cleavage of palytoxin molecule, including the precursor formula C 129 H 225 KN 3 O 54 in the element con-strains (errors 95 ppm in most cases) [16][17][18]. A more thorough examination revealed that the alternative formula C 129 H 224 CaN 3 O 54 could be assigned to the precursor, that is to say the ion of m/z 906.8 could be a palytoxin calcium adduct in place of a potassium adduct; in this way, the unassigned ions of the MS n spectra could all be interpreted as calcium-containing fragments deriving from reasonable cleavages of palytoxin molecule.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most informative results were obtained by interpretation of MS n spectra of the triply-charged ion of m/z 906.8; this ion, previously assigned to [M + 2H + K] 3+ [18], had to be reassigned since most of the fragments contained in its MS n spectra were not consistent with any reasonable cleavage of palytoxin molecule, including the precursor formula C 129 H 225 KN 3 O 54 in the element con-strains (errors 95 ppm in most cases) [16][17][18]. A more thorough examination revealed that the alternative formula C 129 H 224 CaN 3 O 54 could be assigned to the precursor, that is to say the ion of m/z 906.8 could be a palytoxin calcium adduct in place of a potassium adduct; in this way, the unassigned ions of the MS n spectra could all be interpreted as calcium-containing fragments deriving from reasonable cleavages of palytoxin molecule.…”
Section: Resultsmentioning
confidence: 99%
“…O. ovata blooms have repeatedly occurred in subsequent years in Italy as well as along the Mediterranean coasts of Spain, France, and Greece [11]. Putative palytoxin and several new palytoxin-like compounds, named ovatoxin-a, -b, -c, -d, and -e, were identified by our group in both natural and cultured O. ovata samples based on comparison of their HR LC-MS and MS 2 behavior with that of palytoxin [9,[16][17][18]. In these early studies, elemental composition of ovatoxins was provided together with preliminary information on their structures, which allowed only including ovatoxins within the palytoxin group of toxins.…”
Section: Cidmentioning
confidence: 91%
“…siamensis and Prorocentrum lima were toxic to Artemia franciscana. The toxicity of both species is well documented (Murakami et al, 1982;Rhodes et al, 2000;Bravo et al, 2001;Foden et al, 2005;Ciminiello et al, 2006Ciminiello et al, , 2008Mohammad-Noor et al, 2006;Aligizaki et al, 2008aAligizaki et al, , 2009Vale et al, 2009). Differences in the toxic character of a species can be due to the presence of multiple cryptic species within a morphospecies, as reported by Richlen et al (2008) for Gambierdiscus, or because the same species of microalgae may present varying toxicity depending on physiological status, environmental conditions or even between populations in different areas (Guerrini et al, 2009).…”
Section: Toxicitymentioning
confidence: 96%
“…Gambierdiscus was first found in tropical and subtropical waters but has recently been reported from temperate waters of the Mediterranean Sea (Aligizaki & Nikolaidis, 2008) and the Canary Islands (Aligizaki et al, 2008b). Outside tropical and subtropical areas, Ostreopsis is very frequent and well-documented in the Mediterranean Sea (Vila et al, 2001;Turki, 2005;Aligizaki & Nikolaidis, 2006;Ciminiello et al, 2006;Mangialajo et al, 2008;Totti et al, 2010) and reports of blooms in temperate waters have increased in recent years (Shears & Ross, 2009;Rhodes, 2010). Coolia and Prorocentrum appear to be more widely distributed, extending to colder waters than Gambierdiscus and Ostreopsis (Faust, 1991;Bravo et al, 2001;Levasseur et al, 2003;Nascimento et al, 2005;Maranda et al, 2007;Vale et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…4), a PTX analog (Rhodes et al 2002;Taniyama et al 2003;Ukena et al 2001;. Recently, PTX and a new analogue, Ovatoxin-a have been identified in the Mediterranean Sea during a massive bloom of the dinoflagellate Ostreopsis ovata (Ciminiello et al 2006;Ciminiello et al 2008). Thus, at present at least two distinct dinoflagellates belonging to the same genus are known to produce PTX and analogues.…”
Section: Palytoxinsmentioning
confidence: 99%